2018
DOI: 10.1038/s41443-018-0068-9
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction among patients with chronic brucellosis

Abstract: The prevalence of ED among patients with chronic brucellosis is high. Low serum level of testosterone and DM are associated with ED among such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Our study found that the most common clinical manifestations in BPA were fever and dysuria, consistent with other studies. [20][21][22] The fever might be caused by inflammatory mediators in the blood, and the enlarged prostate might cause dysuria. Among our BPA cases, 37.5% had concurrent seminal vesicle infections, and one patient had epididymitis.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that the most common clinical manifestations in BPA were fever and dysuria, consistent with other studies. [20][21][22] The fever might be caused by inflammatory mediators in the blood, and the enlarged prostate might cause dysuria. Among our BPA cases, 37.5% had concurrent seminal vesicle infections, and one patient had epididymitis.…”
Section: Discussionmentioning
confidence: 99%
“…Only one woman was complicated by vaginitis and cervicitis, manifested by increased leucorrhea, menstrual irregularities and lower abdominal distension (Zhou et al, 2020). Epididymitis often coexists with orchitis, called epididymal-orchitis, and is clinically characterized by persistent fever, acute scrotal pain, swelling and congestion, and may be accompanied by rare testicular abscesses, atrophy and oligospermia (Gozdas and Bal, 2020).Safwat et alfound a significantly impaired reproductive system and a higher prevalence of erectile dysfunction (ED) in patients with chronic brucellosis, accounting for 70% of cases, and associated with testicular atrophy and serum decreased serum testosterone levels (Safwat et al, 2018).…”
Section: Genitourinary Systemmentioning
confidence: 99%